2019
DOI: 10.18553/jmcp.2019.25.10.1133
|View full text |Cite
|
Sign up to set email alerts
|

Cost-Effectiveness Analysis of Adjuvant Neratinib Following Trastuzumab in Early-Stage HER2-Positive Breast Cancer

Abstract: BACKGROUND: Disease-free survival (DFS) in early-stage human epidermal growth factor receptor 2 (HER2)-positive breast cancer is significantly greater with the addition of neratinib after adjuvant trastuzumab versus no additional therapy. However, it remains uncertain whether these survival gains represent good value for the money, given the substantial cost of neratinib.OBJECTIVE: To evaluate clinical and economic implications of adding neratinib after adjuvant trastuzumab based on results from the phase III … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 44 publications
0
10
0
Order By: Relevance
“…Ner was initially approved for patients with early-stage HER2-positive breast cancer within 2 years of trastuzumab therapy. 12 Schwartz et al 27 constructed a three-state Markov model to evaluate the cost-effectiveness of adjuvant neratinib following trastuzumab in early-stage HER2-positive breast cancer from the U.S. healthcare payer perspective. This study found that the estimated ICER was $416 106 per QALY gained, and neratinib would need an 85% reduction in price to be cost-effective at a WTP threshold of $150 000.…”
Section: Discussionmentioning
confidence: 99%
“…Ner was initially approved for patients with early-stage HER2-positive breast cancer within 2 years of trastuzumab therapy. 12 Schwartz et al 27 constructed a three-state Markov model to evaluate the cost-effectiveness of adjuvant neratinib following trastuzumab in early-stage HER2-positive breast cancer from the U.S. healthcare payer perspective. This study found that the estimated ICER was $416 106 per QALY gained, and neratinib would need an 85% reduction in price to be cost-effective at a WTP threshold of $150 000.…”
Section: Discussionmentioning
confidence: 99%
“…This is likely a result of provider education and standardized therapy care plans that include anti-diarrheal prophylaxis that are used across our practice sites. In further contrast to the utilization of adjuvant pertuzumab, Schwartz et al found that adjuvant neratinib was not cost-effective, even in this high-risk group, based on the 5-year data from the ExteNET study [ 30 ]. Patients and providers may have concerns about potential toxicity with neratinib and a modest decrease in the risk of recurrence and ultimately choose not to initiate therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Conducting a formal costeffectiveness analysis to guide the selection of an optimal targeted adjuvant therapy was beyond the scope of this guideline; however, several manuscripts have analyzed the cost effectiveness of targeted therapies for breast cancer. [16][17][18][19][20][21][22]…”
Section: Cost Considerations In the Selection Of Optimal Adjuvant Che...mentioning
confidence: 99%